Polish Palaeobotany: 750 Million Years of Plant History as Revealed in a Century of Studies. Palaeozoic Macrofossils - Grzegorz Pacyna; Maria Barbacka (Acta Societatis Botanicorum Poloniae, 2022)
During the Palaeozoic Era, plants conquered the land and covered greater and greater areas from coastal lowlands to highlands. Palaeobotanical data based on macroremains from Polish Palaeozoic strata complete and enrich the picture of these processes. Knowledge about Polish Palaeozoic macrofloras developed significantly in the last hundred years but is very unevenly distributed among successive geological periods. Ordovician and Silurian macrofossils are single finds. Cores from deep boreholes provided significant material for recognition of Early Devonian plants. Carboniferous floras, especially from coal measures, are best known, as they are most numerous in taxa and specimens. Permian floras are very rare. Based on Devonian and Carboniferous fossils, many new, evolutionarily important taxa were proposed and have entered world science.